DAMPAK STRATEGI GREEN MARKETING, KUALITAS PRODUK DAN BRAND IMAGE TERHADAP PERILAKU KONSUMEN - Rahmawati, Meylin (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2022)
This study aims to examine the effect of green marketing, product quality, and brand image on purchasing decisions for Oriflame products (a case study of female students in Tarakan City). In this study, we used a quantitative approach to the survey method by using a questionnaire. The sampling method used is nonprobability sampling with purposive sampling technique. The sample in this study was composed of female students in Tarakan City who had used, bought, and knew about Oriflame cosmetic products, with a total sample size of 190 respondents. The analytical method used is multiple regression analysis with the help of the SPSS version 21 program. The results of this study indicate that the variables green marketing, product quality, and brand image have a positive and significant effect on purchasing decisions for Oriflame products.